2023
DOI: 10.1037/men0000441
|View full text |Cite
|
Sign up to set email alerts
|

A metasynthesis exploring the role of masculinities in close male friendships.

Kristin D. Vierra,
Diana R. Beltran,
Rachael D. Robnett

Abstract: Research suggests that certain masculine norms such as toughness, emotional stoicism, and homophobia can make it challenging for boys and men to form close friendships. This is concerning given that boys and men who do not successfully develop close relationships may experience outcomes such as reduced self-esteem and impaired psychological health. The purpose of the current metasynthesis was to synthesize studies that focus on the role of masculine norms in close male friendships. The present study focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Given that men represent fewer than 1% of breast cancer cases, it is not surprising that men’s experience of breast cancer has been an understudied area of research. The authors found that men’s experiences of breast cancer were similar in some ways to those of women but were also uniquely gendered in other ways, such as the stigma of living with a “woman’s disease.” Last, in a metasynthesis of findings from 28 studies, Vierra et al (2023) identified two overarching themes on the function of masculine norms in close male friendships: (a) pressure to enact traditional masculine norms (e.g., through peers’ heterosexist insults) and (b) the use of compartmentalization of friendships to resist masculine norms. Regarding the second theme, participants distinguished between different types of friendships—some that did not afford them the opportunity to challenge traditional masculine norms and others that enabled them to be emotionally intimate.…”
Section: Articles In the Special Issuementioning
confidence: 99%
“…Given that men represent fewer than 1% of breast cancer cases, it is not surprising that men’s experience of breast cancer has been an understudied area of research. The authors found that men’s experiences of breast cancer were similar in some ways to those of women but were also uniquely gendered in other ways, such as the stigma of living with a “woman’s disease.” Last, in a metasynthesis of findings from 28 studies, Vierra et al (2023) identified two overarching themes on the function of masculine norms in close male friendships: (a) pressure to enact traditional masculine norms (e.g., through peers’ heterosexist insults) and (b) the use of compartmentalization of friendships to resist masculine norms. Regarding the second theme, participants distinguished between different types of friendships—some that did not afford them the opportunity to challenge traditional masculine norms and others that enabled them to be emotionally intimate.…”
Section: Articles In the Special Issuementioning
confidence: 99%